2020
DOI: 10.3892/ijmm.2020.4685
|View full text |Cite
|
Sign up to set email alerts
|

miR‑28‑5p inhibits the migration of breast�cancer by regulating WSB2

Abstract: MicroRNAs (miRNAs or miRs) play an important role in the tumorigenesis and progression of breast cancer. However, the function of miR-28-5p in breast cancer migration has yet to be determined. In the present study, Human MicroRNA Expression database (HMEd) analysis revealed that the expression level of miR-28-5p was significantly lower in breast cancer tissue than in normal breast tissue. Kaplan-Meier plotter (KMPLOT) analysis revealed that the low expression level of miR-28-5p was associated with a poor survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…In this study, we identified TUC338 as a cytoplasmic lncRNA in DLBCL cells that could sponge miR-28-5p and inhibit its activity. miR-28-5p is a well-documented tumor suppressor in various cancer types, including breast cancer [ 25 ], pancreatic cancer [ 26 , 27 ], endometrial cancer [ 28 ], colorectal cancer [ 29 ], and hepatocellular carcinoma [ 30 ]. Here, we found that miR-28-5p level was significantly decreased in human DLBCL tissues, and silencing of miR-28-5p could effectively block the decreased cell malignant phenotype caused by TUC338 knockdown, suggesting that miR-28-5p also plays a tumor-inhibiting role in DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we identified TUC338 as a cytoplasmic lncRNA in DLBCL cells that could sponge miR-28-5p and inhibit its activity. miR-28-5p is a well-documented tumor suppressor in various cancer types, including breast cancer [ 25 ], pancreatic cancer [ 26 , 27 ], endometrial cancer [ 28 ], colorectal cancer [ 29 ], and hepatocellular carcinoma [ 30 ]. Here, we found that miR-28-5p level was significantly decreased in human DLBCL tissues, and silencing of miR-28-5p could effectively block the decreased cell malignant phenotype caused by TUC338 knockdown, suggesting that miR-28-5p also plays a tumor-inhibiting role in DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with that in human breast epithelial cells (HMECs), the expression of miR‐28‐5p in breast cancer cells was significantly decreased. Transfection of miR‐28‐5p mimics could inhibit the migration of MCF‐7 cells, whereas miR‐28‐5p inhibitors had the opposite effect (Ma et al, 2020). Furthermore, CRC was reported to be negatively regulated by miR‐28‐5p (Fan et al, 2020), and insulin‐like growth factor‐1 (IGF‐1) mediated the downregulation of miR‐28‐5p expression in human hepatocellular carcinoma (HCC) (Shi & Teng, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are involved in various viral infectious diseases, such as human immunodeficiency virus-1 (HIV-1) infection (19), human papillomavirus infection (20), SARS-CoV infection (21) and hepatitis B virus infection (20)(21)(22). As mature miRNAs, miR-28-3p and miR-28-5p are derived from the 3' and 5' ends, respectively, of pre-miR-28 and then go on to target different mRNAs, such as WD repeat and SOCS box-containing 2 and forkhead box O1 (23)(24)(25)(26)(27). There is evidence indicating that miRNAs may block RNA virus replication during viral infection (28).…”
Section: Microrna-28-3p Inhibits Angiotensin-converting Enzymementioning
confidence: 99%